Geometric modeling of terry fabric. Issue 2 (20th April 2015) - Singh, Jitendra Pratap; Behera, Bijoya Kumar
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop a 3D geometric model of three-pick terry fabric considering the actual design and structural features of the finished terry fabric. Design/methodology/approach – The model has been developed using SolidWorks CAD system and the output file can be easily simulated in the ANSYS. Dimensions are acquired from the actual terry fabric measurement. Findings – A 3D computational model – to be used for understanding the behaviour of terry fabric during actual use through the simulation in ANSYS. Practical implications – Provides the way to study the yarn and fabric structure behaviour during use through simulation. Originality/value – The research resulted a 3D geometrical model of very complex three-pick terry fabric for very first time for further analysis of terry fabric behaviour during use.